Ultrasonic extraction increases the extraction of antioxidant and citrulline in damaged watermelons in the Comarca Lagunera, México - Jared Borroel García, Victoria; Antonio Alvarado Arroyo, Raúl; Moncayo Luján, María del Rosario; Ortiz Escobar, Tania Breshkovskaya; Lizzeth Guzmán Silos, Tania; García Hernández, José Luis; Ramírez Aragón, Mercedes Georgina (Emirates Journal of Food and Agriculture, 2022)
n this study, the content of lycopene, total phenolics, total flavonoids, antioxidant activity and citrulline in watermelon from different localities of the Comarca Lagunera were determined. In the Comarca Lagunera, watermelon is the second most important crop, representing 9% of the cultivated area at the national level, with a production value of $9,000,000. Watermelon is known to contain high contents of flavonoids and phenolic compounds, which have antioxidant and anti-inflammatory properties; these compounds include metabolites such as lycopene and citrulline. The determination of these components may vary according to the method of cultivation, fertilization, irrigation, and location, as well as the extraction method used. A completely randomized experimental design was used, analyzing three repetitions for each sample obtained. The data obtained in the present study varied according to the method of extraction, for lycopene (41.22 - 8.48 mg g-1 FW), citrulline (161.44 - 71.11 mg g-1 FW), flavonoids (5.05 - 0.17 mg g-1 FW) and phenolics (10.3 - 0.89 mg g-1 FW). The results indicated that there were no significant differences (p ≤ 0.05) for the effect of the variables degree of damage and locality, but there were significant differences for the extraction methods. Therefore, the ultrasound extraction method could be an alternative for the industry due to the increase of active biocompounds that can be obtained, reducing the time of obtaining, the low process costs and the contribution to a sustainable development